(untitled) - Logan, Harriet (New York, NY, 2002)
Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Women in Islam -- Afghanistan; Women -- Afghanistan -- Interviews; Women -- Afghanistan -- Pictorial works; Women -- Afghanistan -- Social conditions; Phụ nữ Hồi Giáo -- Phỏng vấn -- Afghanistan